Nurses’ role in acute coronary syndrome in emergency patients - Santos, Rafael de Carvalho dos; Teixeira , Camile Lourenço da Silva; Dovales , Camilla de Carvalho; Souza , Renata Dantas de; Brazil, Isabela Aparecida Rodrigues; Pereira , Laryssa de Abreu Fialho Silva (Seven Editora, 2023)
Acute coronary syndrome (ACS) is a pathology that annually leads to the death of thousands of people around the world. Every year new statistics emerge, and every year they get worse on the global stage. Thus, the following question was asked: "what would be the role of the nurse in the face of a victim with acute coronary syndrome in the emergency department?" That is why the objective of this study was to describe the performance of nurses in a qualified way in the face of the clinical manifestations of Acute Coronary Syndrome. In view of the severity of the pathology and the high rate of morbidity and mortality, further studies on the subject are extremely relevant to better instruct professionals and disseminate the new protocols for the care of these patients. To do this, we chose to use the methodology in the form of an integrative review, to which throughout the research we came across a total of 35 articles talking about this theme. From this number, we excluded 16 because they were outdated and used 19 to carry out this work. We conclude that good care provided in the emergency room quickly and effectively significantly increases the chances of patient survival and, therefore, we can affirm that the initial approach with emphasis on the prevention of lesions secondary to ischemic myocardial injury is extremely important. Therefore, the health professional should be aware of the signs of poor tissue perfusion, thus preventing these secondary lesions. DOI:https://doi.org/10.56238/sevened2023.004-005